2016
DOI: 10.1136/oemed-2016-103895
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for leptospirosis seropositivity in slaughterhouse workers in western Kenya

Abstract: ObjectivesLeptospirosis has been documented in slaughterhouse workers around the world. Risk factors include smoking and drinking at work, and performing tasks such as cleaning offal. This paper examined risk factors for leptospirosis seropositivity in slaughterhouse workers in western Kenya.MethodsThe study was conducted between May 2011 and October 2012. Questionnaires were used to collect information from workers on demographic data, health and hygiene practices in the slaughterhouse. A commercial ELISA det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 26 publications
3
50
2
2
Order By: Relevance
“…A seroprevalence survey on banked sera of febrile patients treated in a rural clinic in western Kenya recorded seropositivity of 30.9, with 3 % of patients who had been diagnosed with acute lower respiratory infections (ALRI) being found to have acute Q fever [ 17 ]. A study by Cook et al [ 33 ] reported C. burnetii seroprevalence of 4.5 % in abattoir workers in western Kenya while Mwololo et al [ 34 ] found 26.8 % seropositivity in individuals in Bura district where mixed crop farming and pastoralism are practiced. The findings in these studies were recently presented at international conferences [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A seroprevalence survey on banked sera of febrile patients treated in a rural clinic in western Kenya recorded seropositivity of 30.9, with 3 % of patients who had been diagnosed with acute lower respiratory infections (ALRI) being found to have acute Q fever [ 17 ]. A study by Cook et al [ 33 ] reported C. burnetii seroprevalence of 4.5 % in abattoir workers in western Kenya while Mwololo et al [ 34 ] found 26.8 % seropositivity in individuals in Bura district where mixed crop farming and pastoralism are practiced. The findings in these studies were recently presented at international conferences [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study by Cook et al [ 33 ] reported C. burnetii seroprevalence of 4.5 % in abattoir workers in western Kenya while Mwololo et al [ 34 ] found 26.8 % seropositivity in individuals in Bura district where mixed crop farming and pastoralism are practiced. The findings in these studies were recently presented at international conferences [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The source of human infection is direct contact with animal-infected urine or indirect through contaminated water [1,2]. Especially in developed countries, leptospirosis represents an occupational disease associated with particular kind of works (cropper, farmer, veterinarian and slaughterer) [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Mezbaha temizliği yapan dört çalışan ise seronegatif bulundu, kişisel koruyucu ekipman kullanımının yüksek oranda sağlanıyor olmasının bu durumu sağlamış olabileceği düşünüldü. Kenya'da yapılan prevalans çalışmasında mezbaha çalışanlarının mezbahada ne iş yaptıklarından bağımsız olarak iş sırasında sigara içmeleri, yemek yemeleri ya da içmeleri ve sakatatları temizlemeleri mezbaha içinde seropozitiflik riskini arttıran eylemler olarak bulunmuş olup önlük kullanımı koruyucu unsur olarak saptanmıştır (19).…”
Section: Gereç Ve Yöntemunclassified